2004
DOI: 10.1111/j.1439-0507.2004.00986.x
|View full text |Cite
|
Sign up to set email alerts
|

Paranasal sinus aspergillosis: its categorization to develop a treatment protocol

Abstract: A prospective study was conducted in 25 consecutive patients of paranasal sinus aspergillosis to categorize and treat them based on a fixed treatment protocol. The three types of aspergillosis categorized as per definitive criteria were chronic invasive (six), non-invasive (fungus ball) (seven) and non-invasive destructive (12). Adjuvant chemotherapy was employed in non-invasive destructive and chronic invasive disease. Ketoconazole was used in the first variety and itroconazole in the latter. Only two patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Florid granulomatous inflammation is the histological hallmark of this condition. Interestingly, almost all reports come from the Sudan (Milosev et al, 1969;Gumaa et al, 1992;Yagi et al, 1999), Saudi Arabia (Alrajhi et al, 2001) and the Indian subcontinent (Chakrabarti et al, 1992;Ramani et al, 1994;Panda et al, 2004). There are a limited number of reports in the USA, which appear to affect almost exclusively African-Americans (Currens et al, 2002).…”
Section: Rhinosinusitismentioning
confidence: 99%
“…Florid granulomatous inflammation is the histological hallmark of this condition. Interestingly, almost all reports come from the Sudan (Milosev et al, 1969;Gumaa et al, 1992;Yagi et al, 1999), Saudi Arabia (Alrajhi et al, 2001) and the Indian subcontinent (Chakrabarti et al, 1992;Ramani et al, 1994;Panda et al, 2004). There are a limited number of reports in the USA, which appear to affect almost exclusively African-Americans (Currens et al, 2002).…”
Section: Rhinosinusitismentioning
confidence: 99%
“…Panda et al divided fungal rhinosinusitis into acute and chronic invasive categories for the following reasons: similar histopathological evidence of mucosal invasion, a fixed treatment protocol for both diseases, and similar clinical manifestations, such as involvement of multiple sinuses and orbital or intracranial involvement [14]. We reported 6 deaths in 55 cases, all found in the CIFRS group.…”
Section: Discussionmentioning
confidence: 73%
“…Cultures on Sabouraud Pétri plates are not always positive, 9 except for Panda et al 7 Treatment of sphenoid sinus non-invasive aspergillosis requires excision through endoscopic endonasal transsphenoidal surgery, or microsurgery. Good results have been achieved without antifungal treatment where authors have found no relapse after surgery alone.…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive destructive aspergillosis occurs in 2.2% to 63% of cases and leads to systemic antifungal-associated surgical removal in some cases. 7,8 Definite diagnosis is actually based on histopathology 3,8 that excision multiple septated fungal hyphae without tissue invasion.…”
Section: Discussionmentioning
confidence: 99%